Awareness Level of Cervical Cancer among Rural Women Attending Manikgonj 250-Bedded District Hospital, Manikgonj - Rahman, Farzana; Bhattacharjee, Avisak (Journal of Enam Medical College, 2019)
Background: Cervical cancer is a typically slow-growing cancer that may not have symptoms, but can be early diagnosed by Pap smear and Visual Inspection of Cervix with Acetic Acid (VIA). The burden of the disease is increasing in developing countries day by day due to the ascending trend of transmissible diseases such as HIV and Human Papilloma Virus (HPV). Objective: The main aim of this study was to assess the level of awareness regarding cervical cancer among the women attending outpatient department of Manikgonj 250-bedded district hospital, Manikgonj. Materials and Methods: This study was conducted among the women attending the OPD of Obstetrics & Gynaecology Department of Manikgonj 250-bedded district hospital from June, 2017 to October, 2017. The respondents were selected by random sampling. A pre-structured, interview-based data collection sheet was prepared, which was used as a research tool. Data were collected by interview of the patients and then data were gathered, decorated and tabulated after data cleaning and edition. Then the results were presented in tabular and figure forms. As it is a descriptive type of cross-sectional study p value determination was not required to see the level of significance. Results: In this study mean age of 50 respondents was 24.18 ± 6.63 years. The maximum respondents (62%) were from 20−30 years age group. Out of 50 respondents 46% were married and 24% were unmarried. Among the study subjects 84% knew about cervical cancers, 28% respondents knew about the disease from uthan boithok and 26% by electronic and print media. Thirty six percent respondents knew about the risk factors of the disease, 42 (84%) heard about the disease, 60% thought that they are at self risk and 12% respondents underwent screening before. Among those (70.45%) who did not undergo screening blamed not having adequate knowledge about the risk factors. Seventy two percent of total respondents knew that district hospital is a center for screening. Fifty percent women did not have any knowledge regarding vaccination. Conclusion: Majority respondents in this study did not know clearly about cervical cancer, specially its risk factors, vaccination, prevention and clinical profile of the disease. J Enam Med Col 2019; 9(1): 34-40